Identifikasi Komponen Model Pelatihan Pedagogi untuk Meningkatkan Profesionalitas Calon Guru Kejuruan - Rina Febriana (Jurnal Pendidikan Teknologi dan Kejuruan, 2016)
This study aims to develop the components of a pedagogical training model to improve the professionalism of prospective vocational teachers. This study is planned to be undertaken in three years.In the first year it was generated the components and their pedagogical training model tests in the internal scale of Jakarta State University. This study uses a quantitative method that lasted for three years. The determined outcomes of the study in the first year, the second year and the third year are the identification of the components, the model of training pedagogy and the effectiveness evaluation of the model by integrating the prerequisit pedagogical subjects. It will give impacts to the students who has completed the pedagocical course. They will have pedagogic competence to improve their pedagogical professionalism. This study uses the design of research and development by adopting the model of vocational training (skill training for the job). The subjects of the study were the students of the Faculty of Engineering, Jakarta State University. The arranged procedure of the study in the first year consists of: (1) the study of literature, (2) the data collection and the triangulation of data, (3) the description and the analysis of the data. The achieved target in the first year was the identification of the components of pedagogical training model.Penelitian ini bertujuan untuk mengembangkan komponen model pelatihan pedagogi untuk meningkatkan profesionalitas calon guru kejuruan. Studi ini direncanakan akan memerlukan waktu tiga tahun. Pada tahun pertama dihasilkan komponen model pelatihan pedagogik beserta ujicoba pada skala internal UNJ. Penelitian ini menggunakan metode kuantitatif yang berdurasi selama tiga tahun. Luaran penelitian pada tahun pertama adalah identifikasi komponen model pelatihan pedagogik, tahun kedua menghasilkan model pelatihan pedagogi dan tahun ketiga menguji efektivitas model dengan mengintegrasikan mata kuliah kependidikan yang bersifat prerequisit sehingga setiap mahasiswa yang telah menyelesaikan matakuliah kependidikan akan memiliki kompetensi pedagogik yang dapat meningkatkan profesionalitas keguruannya.Penelitian ini menggunakan desain research and development dengan mengadopsi model latihan keterampilan kerja (skill training for the job). Subyek penelitian adalah mahasiswa di Fakultas Teknik Universitas Negeri Jakarta. Tahun pertama menempuh alur sebagai berikut: (1) studi literatur, (2) pengumpulan data lapangan dan triangulasi data, (3) deskripsi dan analisis temuan terhadap komponen model pembelajaran yang terdapat pada pendidikan kejuruan. Target yang dicapai pada tahun pertama yaitu identifikasi komponen model pelatihan pedagogik.